Thermal Imaging for Enhancing Inspection Reliability: Detection and Characterization - M. S., Jadin; Soib, Taib; Shahid, Kabir (InTech, 2012)
Reliable performance of an equipment or structure depends on pre-service quality and in- service degradation of the equipment or structure under operating conditions. The role of non-destructive testing (NDT) is to ensure integrity, and in turn, reliability of equipment or structure. Besides, NDT can also monitor in-service degradation and to avoid premature failure of the equipments/structures and prevent accidents as well as save human life. Up to now, NDT has been used in various fields of applications such as the inspection of